Nghiên cứu giải pháp phát hiện tin giả trên mạng xã hội bằng ngôn ngữ tiếng Việt - Truong Quoc , Dinh; Phan Thi Thuy, Kieu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
In this research, the authors use the information search solution to find real with similar content to the content of the newsletter to be tested, then use cosine measurement to measure and evaluate the news of the test is fake or not. This research uses two datasets for the purpose of determining the value of the parameters of the proposed model as well as testing the accuracy of the model. The real data set collected from the official Vietnamese news sites is the real one. Test datasets are collected from social media posts that have both real and fake news for the purpose of testing the accuracy of the proposed model. Experimental results on the two datasets show that our proposed model can detect fake news.
Keywords: Fake news; Social media; Fake new detection; Summary; Cosine similarity